The Influence of Understanding Tax Regulations, Quality of Fiscal Services, Tax Law Enforcement on Taxpayer Compliance Behavior Moderated Taxpayer Awareness - Nurkhaerun Nisa; Sumarlin; Nur Rahmah Sari (Journal of Applied Taxation and Policy, 2026)
Tax is the main source of state revenue that plays a crucial role in supporting national development; however, individual taxpayer compliance remains a challenge in Indonesia. This study aims to examine the effect of understanding tax regulations, quality of fiscal services, and tax law enforcement on taxpayer compliance behavior, with taxpayer awareness as a moderating variable. This research employed a quantitative approach using a survey method. The population consisted of individual taxpayers registered at the Tax Counseling and Consultation Office (KP2KP) Pinrang, with 102 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that understanding tax regulations, quality of fiscal services, and tax law enforcement have a positive and significant effect on taxpayer compliance behavior. Furthermore, taxpayer awareness is proven to strengthen the influence of these variables on taxpayer compliance. These findings suggest that improving tax compliance requires not only effective regulations and law enforcement but also increased taxpayer awareness. This study contributes to the literature on tax compliance behavior and provides practical implications for policymakers in designing strategies to enhance sustainable taxpayer compliance.